Photobiomodulation using high- or low-level laser irradiations in patients with lumbar disc degenerative changes: disappointing outcomes and remarks - Taradaj J (Dove Medical Press, 2018)
Jakub Taradaj,1,2 Katarzyna Rajfur,3 Barbara Shay,2 Joanna Rajfur,3 Kuba Ptaszkowski,4 Karolina Walewicz,3 Robert Dymarek,5 Mirosław Sopel,5 Joanna Rosińczuk5 1Department of Physiotherapy Basics, Academy of Physical Education, Katowice, Poland; 2College of Rehabilitation Sciences, University of Manitoba, Winnipeg, MB, Canada; 3Public Higher Medical Professional School, Opole, Poland; 4Department of Clinical Biomechanics and Physiotherapy in Motor System Disorders, Wroclaw Medical University, Wroclaw, Poland; 5Department of Nervous System Diseases, Wroclaw Medical University, Wroclaw, Poland Background: Laser therapy seems to be a beneficial physical agent for chronic low back pain (LBP), and it is commonly used in the clinical rehabilitation practice. However, there are still no indisputable and clearly defined protocols and practical guidelines, and further, the methodology of the previous reports leaves many unsatisfied and raises some reservations. Objective: The aim of this study was to evaluate the effectiveness of low-level laser therapy (LLLT) and high-intensity laser therapy (HILT) in patients with lumbar disc degenerative changes based on the analysis of the short- and long-term results and in comparison with the placebo effect. Design: This study was a prospective and placebo-controlled clinical trial. Materials and methods: A group of 68 participants were qualified for the therapy and were assigned to four comparative groups in the order they volunteered: HILT of 1,064 nm, 60 J/cm2, 10 minutes (HILT); sham (HILT placebo); LLLT of 785 nm, 8 J/cm2, 8 minutes; and sham (LLLT placebo). The following tests were used to assess the effectiveness of treatment: 1) the visual analogue scale; 2) the Laitinen Questionnaire Indicators of Pain; 3) the Oswestry Disability Index; 4) the Roland–Morris Disability Questionnaire; 5) Lasegue test; and 6) Schober’s test. All measurements were carried out before and after irradiations (3 weeks) and in follow-ups (1 and 3 months). Results: After applying verum or placebo laser irradiation, therapeutic progress was observed in all comparative groups; however, no statistically significant differences were observed among the procedures. Conclusion: The high- and low-energy laser therapy methods used in the present article are ineffective in relation to patients with lumbar disc degenerative changes in both the short- and long-term perspectives and do not show a significant advantage over the placebo effect. Keywords: laser therapy, low back pain, lumbar disc degenerative changes, photobiomodulation therapy